The Physiology and Pathophysiology of T-Tubules in the Heart - Setterberg, Ingunn E.; Le, Christopher; Frisk, Michael; Perdreau-Dahl, Harmonie; Li, Jia; Louch, William E. (Frontiers in Physiology, 2021)
In cardiomyocytes, invaginations of the sarcolemmal membrane called t-tubules are critically important for triggering contraction by excitation-contraction (EC) coupling. These structures form functional junctions with the sarcoplasmic reticulum (SR), and thereby enable close contact between L-type Ca2+ channels (LTCCs) and Ryanodine Receptors (RyRs). This arrangement in turn, ensures efficient triggering of Ca2+ release, and contraction. While new data indicate that t-tubules are capable of exhibiting compensatory remodeling, they are also widely reported to be structurally and functionally compromised during disease, resulting in disrupted Ca2+ homeostasis, impaired systolic and/or diastolic function, and arrhythmogenesis. This review summarizes these findings, while highlighting an emerging appreciation of the distinct roles of t-tubules in the pathophysiology of heart failure with reduced and preserved ejection fraction (HFrEF and HFpEF). In this context, we review current understanding of the processes underlying t-tubule growth, maintenance, and degradation, underscoring the involvement of a variety of regulatory proteins, including junctophilin-2 (JPH2), amphiphysin-2 (BIN1), caveolin-3 (Cav3), and newer candidate proteins. Upstream regulation of t-tubule structure/function by cardiac workload and specifically ventricular wall stress is also discussed, alongside perspectives for novel strategies which may therapeutically target these mechanisms.